A pilot study about on-farm assessment of health and welfare in rabbits kept in different housing systems - Trocino, Angela; Menegon, Francesca; Zomeño, Cristina; Pasqualin, Dario; Cunial, Giovanni; Xiccato, Gerolamo; Pirrone, Fabrizio; Bertotto, Daniela; Bortoletti, Martina; Dorigo, Francesco; Lavazza, Antonio; Di Martino, Guido (Frontiers in Veterinary Science, 2022)
This study compared on-farm health and welfare of rabbits kept in four different housing systems (standard, breeding cages for reproducing does and their litters associated with bicellular cages for growing rabbits; dual-purpose cages for both reproducing does with their litters and growing rabbits; enriched cages for both reproducing does with their litters and growing rabbits; park systems, which used single modules of a park for reproducing does with their litters and four joined modules for growing rabbits), using resource, management and animal-based measures. A total of 12 commercial farms (3 farms/4 housing system) were visited during three seasons (summer, autumn, winter) on two occasions, a pre-weaning visit for recordings on reproducing does and litters, and a pre-slaughtering visit for recordings on growing rabbits. At the pre-weaning visit, reproducing does in farms using the standard housing system showed the lowest live weight (4431 g vs. 4765 g vs. 4914 g and 4968 g; P<0.001) and the worst body condition (1.91 vs. 1.94, 2.00 and 2.09; P<0.001) compared to does in farms with dual purpose cages, enriched cages, and parks, respectively. The lowest litter size was found in farms using the standard housing system and dual-purpose cages compared to farms with enriched cages and park systems (8.08 and 8.21 vs. 8.61 and 9.18; P<0.001). The prevalence of health concerns did not differ among does and litters kept in the different housing systems. At the pre-slaughtering visit, live weight of growing rabbits decreased from those in farms with enriched cages to those using dual purpose cages, parks and bicellular cages (2584 g vs. 2509 g vs. 2464 g and 2456 g; P<0.001). Regarding health issues in growing rabbits, a higher prevalence of dermatomycosis was found in farms with dual purpose cages and parks. Overall, the outcomes of the present study did not highlight major differences in welfare and health of reproducing does and their kits as well as of growing rabbits in farms using different housing systems.